Investigation of antibacterial and antifungal properties of benzene sulfonamide derivatives by experimental and computational studies - Özge Kapısuz; Mithun Rudrapal; Ülküye Dudu Gül; Sanket S. Rathod; Mesut Işık; Mustafa Durgun; Johra Khan (Chemical Physics Impact)
This study investigates the antibacterial and antifungal properties of eight benzene sulfonamide derivatives synthesized and reported in our previous study using a combination of experimental and computational methods. In antimicrobial activity, the MIC values of all the eight tested compounds were approximately 125.00 μg/mL against eight bacterial and three fungal strains. However, the compound 8 was found to exhibit remarkable activity (MIC=31.25 μg/mL) against E. faecalis (bacteria) and C. parapsilosis (fungi) compared to the MIC values of rest of the compounds. Results of in-silico drug-likeness and pharmacokinetic (ADMET) assessment reveal that all the title compounds met the compliance of criteria of drug-likeness rules and exhibited zero violations across. Results of docking study demonstrates that the compound 8 showed the highest binding affinity (-8.7 kcal/mol) among the compounds against S. aureus TyrRS, whereas against S. aureus DHFR, compound 2 exhibited the highest binding afinity of -8.5 kcal/mol. Among the compounds docked against C. albicans DHFR and C. albicans N-myristoyl transferase, compound 8 demonstrated the highest binding affinity of -8 kcal/mol and -8.9 kcal/mol, respectively. The results of antibacterial and antifungal experiments substantiate the predictions made by computational studies and provide empirical evidence of antibacterial and antifungal potential of the reported benzene sulfonamide derivatives.